Learning Effectiveness, New Normal the Purpose of This Study was to Determine the Effectiveness of Sport Education Learning in he New Normal Era at MAN 3 Jombang High School in Face-too-Face Learning - Faisol Hamid; Kahan Tony Hendrawan (Universitas Majalengka, 2023)
The purpose of this study is to determine the effectiveness of PJOK Learning in the New Normal Era of MAN 3 Jombang in alternating face-to-face learning. This research is a quantitative descriptive study. This research method uses a survey method, the data collection method used in this study uses the FCE Formative Class Evaluation questionnaire. The population in the study was class XI MAN 3 Jombang which amounted to 835 students. This study used a random sampling technique where researchers took class XI MIPA students into a sample of 160 students. The instrument used in this study is the FCE Formative Class Evaluation questionnaire, to obtain various questionnaire data used in this study is to use a likert scale. The results of this study show that the effectiveness in PJOK learning at MAN 3 Jombang is effective / achieved, due to existing results, from the four indicators, namely yield indicators, willingness indicators, method indicators and cooperation indicators. Regarding the survey of the effectiveness of PJOK learning in the new normal era at MAN 3 Jombang in class XI MIPA shows that the effectiveness of face-to-face PJOK learning alternately is still carried out effectively or achieved.